Basic Concepts and Paradigms of Academic Leadership - Juli Rachmadani Hasibuan; Yeni Erlita; Masitowarni Siregar; Fahri Hawani (LOKAKARYA, 2026)
Academic leadership has emerged as a pivotal factor in the advancement and efficacy of higher education institutions. Universities function as knowledge-centric entities and necessitate leadership that integrates leadership competencies, academic expertise, and a strategic institutional vision. This study examines the essential concepts and evolving paradigms of academic leadership within higher education. The discourse centers on four key aspects: the essence of leadership, the distinction between leadership and management, paradigms of academic leadership within universities, and the function of scientific leadership in applied linguistics. This essay employs a conceptual and analytical framework to examine pertinent international literature on leadership and management within higher education. This study employs a qualitative descriptive approach using a conceptual literature review, drawing on relevant international scholarly sources to analyze leadership practices in higher education. The results show that academic leadership goes beyond just being in charge of the office; it also includes intellectual impact, research guidance, and working together with other scholars. Modern universities are increasingly employing decentralized and collaborative management frameworks to address challenges such as globalization, digital transformation, and research competitiveness. In applied linguistics, for example, academic leadership is also very important for setting research objectives and encouraging new ideas in the field. Enhancing academic leadership necessitates that universities incorporate intellectual authority, collaborative governance, and strategic management techniques to foster the sustained advancement of institutions.